Performance indicators of public private partnership in Bangladesh: An implication for developing countries. Issue 1 (31st December 2018) - Hossain, Mohammad; Guest, Ross; Smith, Christine
Abstract : Purpose: The purpose of this paper is to develop weights of key performance areas (KPAs) and performance indicators for public private partnerships (PPPs) in Bangladesh. Since a variety of PPP arrangements is observable, different performance measurement approaches exist in the literature. However, analysing the relative importance of indicators influencing the performance score of particular projects using the perspective of developing countries remains unexplored. Design/methodology/approach: The authors' method involves application of the analytical hierarchy process (AHP) to develop weights for eight KPAs for which 41 contributing performance indicators have been developed. In total, 68 respondents (62 per cent of the PPP practitioners in Bangladesh) participated in a structured questionnaire survey and their judgements have been found to be consistent, using consistency ratios, a geometric consistency index and one-way ANOVA test. Findings: "Feasibility analysis", "life cycle evaluation and monitoring" and "optimal risk allocation" are the most significant performance indicators in Bangladesh. "Financing" is the most important KPA, followed by "planning and initiation" and "transparency and accountability". Interestingly, unlike the cost, time and quality measures of the public sector comparator analysis used in most developed countries, a different set of indicators and KPAs are found dominant. Research limitations/implications: This suggests that performance indicators and their weights may differ for developing countries. Future research could usefully focus on testing this model in different countries and applying it to derive performance scores for individual PPPs. Originality/value: An application of AHP in determining weights of the performance indicators represents a major contribution to the literature on PPP performance measurement in the developing countries including Bangladesh.